Administration of a Next-Generation Probiotic Escherichia coli Nissle 1917-GLP-1 Alleviates Diabetes in Mice With Type 1 and Type 2 Diabetes - Jie Luo; Yilin Fang; Zhanghua Qi; Fengyang Cui; Hong Hu; Shengjie Li; Tingtao Chen; Hongyan Zhang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Diabetes mellitus (DM) is a persistent and steadily progressing metabolic condition distinguished by unregulated high levels of blood glucose. GLP1 receptor agonists have recently gained recognition as first-line therapies in selected instances, as per the updated ADA guidelines, highlighting their efficacy not only in glycemic control but also in their broader health benefits. Nonetheless, the efficacy of GLP-1 is limited by its brief duration of action, rapid clearance from the body, and challenges associated with subcutaneous administration. In this study, we examined the potential diabetes-mitigating effects of a genetically engineered strain of Escherichia coli Nissle 1917 (EcN)-GLP-1, previously developed by our group. We utilized mouse models for both Type 1 diabetes mellitus (T1DM) and Type 2 diabetes mellitus (T2DM) to assess its efficacy. In the case of T1DM mice, the results revealed that EcN-GLP-1 resulted in a notable decrease in blood glucose levels. Furthermore, it exhibited a protective influence on the structural integrity of islet β-cells; downregulated the expressions of key inflammatory markers such as TLR-4, p-NF-κB/NF-κB, and Bax/Bcl-2; promoted the insulin secretion; and reinstated the perturbed diversity of microbial species to a normal state. Similarly, EcN-GLP-1 had a pronounced impact on T2DM mice, manifesting increased presence of islet β-cells, decreased inflammatory response and apoptosis, and regulation of lipid metabolism in the liver. In summary, the genetically modified EcN-GLP-1 strain demonstrates the ability to alleviate diabetes by enhancing the islet β-cell population, mitigating inflammatory reactions and apoptosis, optimizing liver lipid metabolism, and reinstating a balanced microbial diversity. These findings hold promise as a potential avenue for treating DM.